Training and Detraining Effects of Institutional Group Exercise on Upper Extremity Motor Function - Yiling LIN; Minghsia HU; Hongzhe ZHANG; Mingde LI (康复学报)
Objective:To examine the training and detraining effects of a group exercise activity program for the institutional residents with functional dependency.Method:Residents with functional dependency from two nursing homes (older than 60 years) were recruited.A total of 41 residents were randomly assigned to the intervention (n=18) or the control groups (n=23). The intervention group received group exercise three times per week for ten weeks, the control group maintained the original life style in the institute. Outcome measures included passive range of motion (PROM), muscle strength and upper extremity motor function. The measures were assessed at baseline (pre-test), after 11 weeks (post-test), and at 23 weeks follow-up.Result:At the end of the trial, the exercise subjects demonstrated significant improvement on ROM, muscle strength and upper extremity motor function over the control group (P<0.05). After 12 weeks detraining, all training induced gains were lower than post-test levels in the exercise group. Both muscle strength and upper extremity motor function had returned to baseline levels after four weeks of detraining (P<0.01). Most measurements of ROM of the upper extremity also returned to baseline with 12 weeks of detraining.Conclusion:Group exercise training provided benefits on muscle strength, motor function and range of motion for institutionalized residents with ADL dependency. The cessation of training resulted in a significant decrease and return to baseline status in the upper extremity ROM, muscle strength and motor function of upper extremity among the institutionalized residents within one month who previously undertook the group exercise training. It is suggested that the institutionalized residents maintain regular physical activity training to prevent functional decline.